(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is a global leader in the agricultural industry, which supports well over half of thecountry’s population. India is the world’s greatest producer of milk, pulses, and spices as well as havingthe largest cow herd (buffaloes), and the largest area cultivated with wheat, rice, and cotton. Producingat a high level, it ranks second in the world for a wide variety of crops, including fresh produce, tea,farmed fish, cotton, sugarcane, wheat, rice, and sugar. About half of India’s population finds work in theagricultural industry, which has the second-largest agricultural acreage in the world. Farmers play acrucial role in this industry since they produce the food we eat. Following a decline in expenditure due toa pandemic, consumer spending in India is expected to rebound in 2021, growing by as much as 6.6.Due to its enormous potential for value addition, especially within the food processing sector, the Indianfood industry is set for enormous expansion, increasing its contribution to global food commerce everyyear. In terms of production, consumption, export, and projected growth, the Indian food processingindustry is rated sixth. This sector accounts for 32 of the overall food market in India. This researchaims to compare the agricultural sectors of the Indian states of Rajasthan and Madhya Pradesh.